Diverse dimensions of Yoga - Ananda Balayogi Bhavanani (Wolters Kluwer Medknow Publications, 2014)
Yoga is a word very commonly used in the world today and carries various connotations depending on its usage. It has been defined in various manners as an art and science, as well as the process of conscious evolution. All human beings can gain a lot from the bountiful dimensions of Yoga, which enables them to manifest their inherent divinity, the universal potentiality that lies dormant unless channelized. "All souls are potentially divine," said Swami Vivekananda and, indeed, they are. This article aims to elucidate the diverse dimensions of Yoga that include the dimensions related to Indian culture as well as those associated with health, therapy, society, education, and research. Various physical, mental, emotional, and spiritual benefits attainable through Yoga are explained in detail, highlighting the multiple sub-dimensions of these major fields. Yoga, which emphasizes the universal, is a perfect foil to those human activities which glorify the personal. In short, it may be safely said that the practice of Yoga as a unified whole helps the individual shift from an "I"-centric approach to a "we"- centric approach. The beauty of Yoga is that these abstract principles become concrete by the daily practice of the techniques available in the integrated system. Once the "seed of Yoga" finds fertile soil, these concepts grow naturally, slowly but surely taking root in all aspects of life.